The Massachusetts Hepatitis C Testing Cascade, 2014-2016. (June 2019) - Vo, Quynh T; Onofrey, Shauna; Church, Daniel; Cranston, Kevin; DeMaria, Alfred; Klevens, R Monina
Objectives: To characterize hepatitis C testing in Massachusetts and guide stakeholders in addressing the needs of people living with hepatitis C. Methods: All persons with a positive laboratory report for anti-hepatitis C virus (HCV) antibody, between 2014 and 2016, were included in the testing cascade. Outcomes were HCV tests received after a positive anti-HCV antibody test: nucleic acid test or genotype test. Logistic regression analyses were performed to determine factors associated with progression through the HCV testing cascade. Results: Among those reported anti-HCV antibody positive, a total of 13 194 (61%) cases had a subsequent RNA-based test, and 79% (10 374/13 194) were confirmed with current, active HCV infection. For confirmed HCV cases, 44% (4557/10 374) had a genotype identified. The median time from an antibody-positive test to a RNA-based test was 29 days (interquartile range [IQR] = 7-151). Differences in moving through the testing cascade were observed by birth cohort and race/ethnicity. Conclusions: Improved surveillance capture of demographic information is needed to help public health agencies ensure equity in HCV diagnosis and linkage to care.